RE-ENERGIZING STUDENTS’ MOTIVATION BY GIVING FEEDBACK THROUGH ONLINE LEARNING PLATFORM - Suci Maharani (Universitas Muhammadiyah Prof. DR. HAMKA, 2021)
ABSTRACT Feedback takes crucial parts in teaching and learning process. Moreover, feedback is such information given to the learners in order to help them in achieving the learning objective. This is a case study that has aims to know the teachers and students perspective in the use of feedback through online learning platform to re-energize motivation as well as the reflection of teachers’ perspective in implementation. The data of this study are interview and observation. The finding of this study revealed that feedback gives positive effect for learners in learning English although through learning platform. This study also found that feedback also elicits the learners’ motivation, so that it helped them to improve their English ability. This study also found that the teacher’s perspective reflected the implementation of feedback in teaching English. It also had contribution to improve learners’ English ability and to support the development of teaching English in teaching learning online. Keyword: Feedback, Students’ Perspective, Teacher’s Perspective